Revealing Physical Mechanisms of Spatial Pattern Formation and Switching in Ecosystems via Nonequilibrium Landscape and Flux - Jie Su; Wei Wu; Denis D. Patterson; Simon Asher Levin; Jin Wang (Advanced Science, 2025)
Abstract Spatial patterns are widely observed in numerous nonequilibrium natural systems, often undergoing complex transitions and bifurcations, thereby exhibiting significant importance in many physical and biological systems such as embryonic development, ecosystem desertification, and turbulence. However, how spatial pattern formation emerges and how the spatial pattern switches are not fully understood. Here, a landscape‐flux field theory is developed using the spatial mode expansion method to uncover the underlying physical mechanism of the pattern formation and switching. The landscape and flux field are identified as the driving force for spatial dynamics and applied this theory to the critical transitions between spatial vegetation patterns in semi‐arid ecosystems, revealing that the nonequilibrium flux drives the switchings of spatial patterns. The emergence of pattern switching is revealed through the optimal pathways and how fast this occurs via the speed of pattern switching. Furthermore, both the averaged flux and the entropy production rate exhibit peaks near pattern switching boundaries, revealing dynamical and thermodynamical origins for pattern transitions, and further offering early warning signals for anticipating spatial pattern switching. This work thus reveals physical mechanisms on spatial pattern‐switching in semi‐arid ecosystems and, more generally, introduces a useful approach for quantifying spatial pattern switching in nonequilibrium systems, which further offers practical applications such as early warning signals for critical transitions of spatial patterns.